Cooling of a Partially Elastic Isothermal Surface by Nanofluids Jet Impingement - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Asme, 2018)
Numerical study of nanofluid jet impingement cooling of a partially elastic isothermal hot surface was conducted with finite element method. The impingement surface was made partially elastic, and the effects of Reynolds number (between 25 and 200), solid particle volume fraction (between 0.01 and 0.04), elastic modulus of isothermal hot surface (between 10 4 and 10 6), size of the flexible part (between 7.5 w and 25 w), and nanoparticle type (spherical, cylindrical, blade) on the fluid flow and heat transfer characteristics were analyzed. It was observed that average Nusselt number enhances for higher Reynolds number, higher values of elastic modulus of flexible wall, smaller size of elastic part, and higher nanoparticle solid volume fraction and for cylindrical shaped particles. It is possible to change the maximum Nusselt number by 50.58% and 33% by changing the elastic modulus of the hot wall and size of elastic part whereas average Nusselt number changes by only 9.33% and 6.21%. The discrepancy between various particle shapes is higher for higher particle volume fraction.
Keywords: Convection Heat-Transfer; Lid-Driven Cavity; Fluid-Structure Interaction; Natural-Convection; Triangular Cavity; Mixed Convection; Magnetic-Field; Square Cavity; Moving Plate; Circular Jet